Spectroscopy of berylliumlike xenon ions using dielectronic recombination. (28th May 2015) - Bernhardt, D; Brandau, C; Harman, Z; Kozhuharov, C; Böhm, S; Bosch, F; Fritzsche, S; Jacobi, J; Kieslich, S; Knopp, H; Nolden, F; Shi, W; et al.
Abstract: Be-like ions have been investigated employing the resonant electron–ion collision process of dielectronic recombination (DR) as a spectroscopic tool. The experiments were performed at the experimental storage ring in Darmstadt, Germany, using its electron cooler as a target for free electrons. DR Rydberg resonance series for the associated intra-L-shell transitions and were observed with high resolution. In addition to these excitations from the ground state we determined resonances associated with excitations of ions initially in the metastable state. The corresponding excitation energies were determined to be and and . These excitation energies are compared with previous measurements and with recent state-of-the-art atomic structure calculations.